Trichoderma species from China - ZHANG Chu-long; XU Tong (浙江大学学报. 农业与生命科学版, 2004)
Seventeen species of Trichoderma, isolated from soil or tree bark from China are identified based on morphological and physiological characters, and from their phylogenetic position inferred from parsimony analyses of nucleotide sequences of the internal transcribed spacer regions of the rDNA cluster (ITS1 and 2) and partial sequences of translation elongation factor 1-alpha (tefl). There were T. citrinoviride, T. longibrachiatum, T. sinensis in section Longibrachiatum, T. atroviride, T. koningii, T. viride, T. asperellum, T. hamatum, T. erinaceum in section Trichoderma, T. harzianum (H. lixii), T. inhamatum, T. velutinum, T. cerinum, T. strictipile, T. spirale, T. virens, H. nigrovirens (Trichoderma sp.) in section Pachybasium. Among them four species: T. asperellum, T. velutinum, T. cerinum, T. spirale were reported firstly in China.In addition, two suspected new taxa (Trichoderma spp.) in Trichoderma section were proposed: Trichoderma sp. 1 (ZAUT261, 4, 4A, 15A, 2C), Trichoderma sp. 2 (2B, 5, 7A, 7B, 9A). Trichoderma sp. 1 was similar to T. hamatum, but the temperature optimum for mycelial growth was lower than that of T. hamatum and the species tended to form hemisphaerical pustule with relatively larger conidia (average length 4.6 μm × 2.8 μm). Trichoderma sp. 2 was distinguished morphologically from related species T. strigosum, T. pubescens, T. erinaceum, T. hamatum and Trichoderma sp. 1 in pustules on CMD without fertile or sterile conidiophore elongation and distinctive phialide shape, the conidiophore branches similar to T. koningii, but the conidia similar to T. viride, subglobose, conspicuously tuberculate.